Examining the System Governing the Passages in the Historical City of Qazvin - Ehsan Dizani; Eisa Esfanjary Kenari (منظر, 2023)
Historical cities are living evidence of human civilization and culture. However, there is still much work to be done to identify and accurately understand such civilizational layers in Middle Eastern historical cities. One of the ambiguities associated with Islamic cities is the researchers’ emphasis on their unsystematic arrangement, to the point where some researchers have suggested that the lack of arrangement in the historical network of streets is proof of its chaos. Some scholars, on the other hand, have denied such disorganization and provided answers to prove that an arrangement exists in historical passages. However, the significance of passages in the historical city has yet to be completely examined and described. This study is an attempt to scrutinize the role of the passages in the historical city of Qazvin using a descriptive-analytical method. In addition, morphology and GIS tools were used to identify and analyze the characteristics of the passages in the historical neighborhoods of the Qazvin. The findings of the study show that the passages of the ancient city have been systematically developed and include perceptual, social, and economic components.